2015
DOI: 10.1177/1756287215621234
|View full text |Cite
|
Sign up to set email alerts
|

Managing chronic bladder diseases with the administration of exogenous glycosaminoglycans: an update on the evidence

Abstract: Although the pathophysiology of acute chronic cystitis and other ‘sensory’ disorders, i.e. painful bladder syndrome (PBS) or interstitial cystitis (IC), often remains multifactorial, there is a wide consensus that such clinical conditions may arise from a primary defective urothelium lining or from damaged glycosaminoglycans (GAGs). A ‘cascade’ of events starting from GAG injury, which fails to heal, may lead to chronic bladder epithelial damage and neurogenic inflammation. To restore the GAG layer is becoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…143 Hyaluronic acid, a mucopolysaccharide, is believed to help restore the normal protective layer of polysaccharides that irradiation can damage. 146 Positive effects on bleeding as well as frequency, urgency, and pain have been reported. 147,148 Hyaluronic acid and hyperbaric oxygen had similar effects on hematuria in one study, with a response rate of 88-75%.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…143 Hyaluronic acid, a mucopolysaccharide, is believed to help restore the normal protective layer of polysaccharides that irradiation can damage. 146 Positive effects on bleeding as well as frequency, urgency, and pain have been reported. 147,148 Hyaluronic acid and hyperbaric oxygen had similar effects on hematuria in one study, with a response rate of 88-75%.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…More episodes of UTI followed, and intravesical glycosaminoglycan (6) and intravesical amikacin (250 mg) adjunctive therapies were given by intermittent catheterization besides intravenous meropenem but failed (Fig. 1).…”
mentioning
confidence: 99%
“…In our laboratory, we tested if the bacteriophage suspension our patient had received from Tbilisi was active against his causative ESBL-producing Klebsiella pneumoniae strain. To this end, we performed the bacteriophage spot test using the plaque assay for identification and enumeration of bacteriophages by the double-layer agar method (6). The spot test, which was performed in duplicates, showed lytic activity of the bacteriophage solution ( Fig.…”
mentioning
confidence: 99%
“…Pro‐inflammatory chemokines, such as interleukin‐8, guide neutrophil granulocytes to the area of urothelial damage. Chronic urothelial damage and neurogenic inflammation (the inflammatory response following chronic insult to the bladder nerve supply after depletion of the GAG layer) has been shown in bladder sections with deficient GAG layers . Histology has also shown that GAG supplements reduce neutrophil transmigration and halt the subsequent inflammatory process …”
Section: Glycosaminoglycansmentioning
confidence: 99%